2019
DOI: 10.1016/j.seizure.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cerebrospinal fluid levels of interleukin-10 in children with febrile seizures

Abstract: A B S T R A C TPurpose: The exact etiology of febrile seizures (FS) is still unclear. However, it is thought that cytokine network activation may have a causative role. Therefore, this study aimed to evaluate the levels of interleukin-12 (IL-12) as a proinflammatory cytokine, interleukin-10 (IL-10) as an anti-inflammatory cytokine, and interferon-β (IFNβ), a marker of toll-like receptor-3 activation as a host response to viruses. These cytokine levels were analyzed in the cerebrospinal fluid (CSF) of children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
1
2
1
Order By: Relevance
“…Children with FS have been demonstrated to have higher levels of pro-inflammatory cytokine than febrile controls; however, our results contradict these previous studies [24][25][26]. Virta et al found that the levels of IL-6 in CSF were considerably more significant in those with FS.…”
Section: Discussioncontrasting
confidence: 99%
“…Children with FS have been demonstrated to have higher levels of pro-inflammatory cytokine than febrile controls; however, our results contradict these previous studies [24][25][26]. Virta et al found that the levels of IL-6 in CSF were considerably more significant in those with FS.…”
Section: Discussioncontrasting
confidence: 99%
“…The technical difficulty of measuring cytokines may, in part, explain the contradictions between the results of the current study and those of earlier studies of cytokine levels in patients with FSs. [7][8][9][10][17][18][19][20][21] In the present study, IL-1RA and IL-6 were the only cytokines that demonstrated significant differences between study patients and control patients. The level of IL-1RA, which is described as a reliable indicator of IL-1 axis activity, rises several hours after proinflammatory cytokines, reaching its peak about 24 h after a seizure; therefore, we chose a sampling time limit of 24 h after a seizure.…”
Section: Discussionsupporting
confidence: 48%
“…Wellmann et al found that the serum copeptin and Von Willebrand factor (VWF) of children with FS were significantly higher than those of the control group ( 3 , 7 ). The levels of proinflammatory cytokines, such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), and anti-inflammatory cytokines, such as interleukin-4 (IL-4), in the peripheral blood of children with FS also exhibited significant changes, suggesting that these inflammatory molecules may play an important role in the pathogenesis of FS ( 8 10 ). These observations suggest that serum levels of some bioactive substances have a specific relation with FS, but so far, none has been clinically recognized and applied.…”
Section: Introductionmentioning
confidence: 99%